Pete the cat and the lost tooth - Dean, James 1957- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2017)
A tooth goes missing while Pete the Cat is helping the Tooth Fairy, and he must find it before it's too late.
105663
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Cats -- Juvenile fiction; Lost articles -- Juvenile fiction; Tooth Fairy (Legendary character) -- Fiction; Lost and found possessions -- Fiction; Juvenile Fiction -- Readers -- Beginner; Juvenile Fiction -- Animals -- Cats; Juvenile Fiction -- Health & Daily Living -- Daily Activities; Readers (Publications); Fiction; Juvenile works